Fe-MOF derived jujube pit like Fe3O4/C composite as sulfur host for lithium-sulfur battery. (1st February 2019) - Fan, Lishuang; Wu, Hexian; Wu, Xian; Wang, Maoxu; Cheng, Junhan; Zhang, Naiqing; Feng, Yujie; Sun, Kening
Abstract: Li-S batteries have shown great potential for next generation energy storage due to the high theoretical specific capacity and low cost. However, the issues of shuttle effect of polysulfide, poor conductivity of sulfur, and volume expansion during lithiation/delithiation seriously restrict the development of Li-S batteries. Inspired by the strong chemical absorption between metal oxides and polysulfides, a jujube pit like Fe3 O4 /C composite derived from iron-based metal-organic framework (Fe-MOF) are applied as efficient sulfur host in Li-S batteries in this work. Benefitting from the strong chemical bond between iron ion and polysulfides, as well as the interaction between oxygen anion and lithium ion, the Fe3 O4 /C composite can immobilize the sulfur and inhibit the diffusion of polysulfides efficiently. In addition, the carbon component not only improves the electrical conductivity, but also serves as buffer layer to accommodate the volume variation upon charging/discharging. Consequently, such Fe3 O4 /C/S cathode shows a high initial specific capacity of 1324 mAh/g at a current density of 0.05 C and could retain a specific capacity of 642 mAh/g after 300 cycles at current density of 1 C, corresponding to a low fading rate of 0.072% per cycle. Highlights: The jujube pit like Fe3 O4 /C composite would anchor polysulfides through both physical and chemical adsorption. The hollow structure of the Fe3 O4 /C composites would furnish adequate space for sulfur reserve as well as provide ample interspace for the volume expansion during lithiation. The Fe3 O4 /C contains abundant carbon improving the conductivity of the material.